Does Sharecropping Affect Productivity and Long-Term Investment? Evidence from West Bengal’s Tenancy Reforms - Deininger, Klaus; Jin, Songqing; Yadav, Vandana (World Bank, Washington, DC, 2013)
Although transfer of agricultural land ownership through land reform had positive impacts on productivity, investment, and political empowerment in many cases, institutional arrangements in West Bengal -- which made tenancy heritable and imposed a prohibition on subleasing -- imply that early land reform benefits may not be sustained and gains from this policy remain well below potential. Data from a listing of 96,000 households in 200 villages, complemented by a detailed survey of 1,800 owner-cum tenants, point toward binding policy constraints and large contemporaneous inefficiency of share tenancy that is exacerbated by strong disincentives to investment. A conservative estimate puts the efficiency losses from such arrangements in any period at 25 percent.